A Production and operations management study on Quickserve Equipment Services, Inc. Signage Division - Ilagan, Gazel Antonette T. (College of Engineering, 2001)
Quickserve Equipment Services, Inc. - Signage Division is an in-house fabrication facility for the signage requirements of the RAMCAR Group of Companies. Currently situated at MLQ St., Manggahan, Pasig City, the company fabricates and assembles (for new stores), refurbishes (for exsiting stores), and services (for existing stores) signages for the entire group, particularly the food group (Kentucky Fried Chicken and Mister Donut). The team documented the company's background, operations strategy, process management, workforce management, capacity planning, facility layout and location, supply-chain management, forecasting, aggregate planning and inventory management. In doing so, the team gathered pertinent data and observations to properly determine and evaluate the company's major problem areas. To aid the team in the identification and analysis of the company's problem areas, several IE tools were utilized such as streamline analysis, Systematic Layout Planning (SLP, capacity analysis, forecasting modeling, and aggregate planning, to name a few. The three major problem areas identified were long lead times of raw materials, jumbled workflow and lack of workspace, and overutilization of workforce. The problem on long lead times of raw materials was addressed by the team by an inventory management solution; the problem on jumbled workflow and workspace by a facility layout and process flow solution; and the problem on overutilization of workforce by an aggregate planning/workforce management solution. After qualitative analysis, the team recommends solution to the problem areas identified. The team recommends that the company implement the alternative EOQ and TB0 per raw materials kit (14 basic units and 0.5 months respectively for all kits-aluminum, board and graphics and electrical). Implementing this recommendation will attain for the company a cost saving of 40.42% for the aluminum kit, 48.89% for the board and graphics kit, and 48.14% for the electrical kit. The team also recommends the re-arrangement of workstations, to address the facility layout problem of the company. This recommendation will lessen the total distance traveled by the product being processed by 28.47%. Lastly the team also recommends the addition of workers to minimize the overtime of current workers. These additional workers will not work on a second shift, instead, they will work during regular time with the current workers. The team recommends the addition of 17 workers working on regular time. These 17 workers are assigned to different departments. After addition of extra workers, the plant utilization was again computed. From the computations, the resulting process utilization is less that one for all processes (unlike the current process utilization showing overutilization of labor and machines) This would give the company a cost saving of 36.47%. Other problem areas were also identified, but since this are beyond the team's resources (time and data available) and the know-how (solution technique beyond the scope of IE 151), the problem areas were recommended as areas for further study. These problem areas are company re-organization, time standards, and forecasting.